2008
DOI: 10.1002/bmc.1117
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an on‐line two‐dimensional reversed‐phase liquid chromatography–tandem mass spectrometry method for the simultaneous determination of prostaglandins E2 and F2α and 13,14‐dihydro‐15‐keto prostaglandin F levels in human plasma

Abstract: We developed and validated an on-line reverse-phase two-dimensional LC/MS/MS (2D-LC/MS/MS) system for simultaneous determination of the levels of prostaglandin (PG) E(2) as well as PGF(2alpha) and its metabolite 13,14-dihydro-15-keto PGF(2alpha) (F(2alpha)-M) in human plasma. Analytes were extracted by a three-step solid-phase extraction. Samples were then analyzed by on-line 2D-LC/MS/MS with electrospray ionization in negative mode. The 2D-LC system is composed of two reverse-phase analytical columns with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…These include PGD 2 , PGJ 2 , PGE 2 , 15-d-PGD 2 , PGA 2 , 15-d-PGJ 2 , PGF 2α , PGF 1α , 11β-PGF 2α , 6-keto-PGF 1α , and 11-d-TXB 2 . Several of these metabolites have been previously detected in different matrices such as cell cultures [32, 33], plasma/serum [35-37], urine [34, 39], rat kidney [43]. Masoodi et al [39] and Yue et al [44] reported measurements of prostanoids in rat brain or cortical tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These include PGD 2 , PGJ 2 , PGE 2 , 15-d-PGD 2 , PGA 2 , 15-d-PGJ 2 , PGF 2α , PGF 1α , 11β-PGF 2α , 6-keto-PGF 1α , and 11-d-TXB 2 . Several of these metabolites have been previously detected in different matrices such as cell cultures [32, 33], plasma/serum [35-37], urine [34, 39], rat kidney [43]. Masoodi et al [39] and Yue et al [44] reported measurements of prostanoids in rat brain or cortical tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid progress of liquid-chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) has facilitated the use of this technology for accurate monitoring of eicosanoid metabolites in biological samples [7]. Previous reports include liquid-liquid extraction for the determination of PGE 2 and LTB 4 in plasma using LC-MS [15], the analysis of four kinds of PGs and LTs in cell culture media by LC-MS [16], an on-line two dimensional reverse-phase LC-MS for the simultaneous determine of PGE 2 , PGF 2a and 13,4-dihydro-15-keto PGF 2a [17], and a LC-MS method for the simultaneous determination of twenty-three eicosanoids [18], a UPLC-MS platform that enables profiling of 122 eicosanoids from human whole blood[19], a targeted HPLC-MS/MS analysis platform for 100 oxylipins and 36 oxylipins was detected from 250 uL human plasma in 26 min[20], a LC–MS/MS method for rapid and concomitant quantification of 26 PUFA metabolites from Caco-2 cells [21], a LC–MS/MS for the simultaneous analysis of arachidonic acid and 32 related metabolites in 1 mL human plasma [22], a online HPLC-MS/MS analyzed more than 20 different oxidized fatty acids and their precursors from 200 uL plasma or urine [23], a fast LC–MS/MS method including on-line SPE and LIT fragment confirmation for the profiling of 7 PUFAs and 94 oxidized metabolites from 200 uL plasma [24]. We previously developed a high-throughput lipidomic analysis of eicosanoids using LC-MS to monitor 141 unique species in a single 22 min analysis [25], and applied it to investigate the human plasma lipidome [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Only 18 pieces of papers were found with the key words “PGE 2 and LC-MS” in Pubmed.gov from year of 2000. Most of them are designed to measure the PGE 2 in cell line [2837] and plasma/serum [3841], hence difficult to be applied for tissue PGE 2 assays (since the endogenous interference is much more complex in the tissue). M.Y.…”
Section: Resultsmentioning
confidence: 99%